2000
DOI: 10.1128/jb.182.7.1794-1801.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus lrgAB Operon Modulates Murein Hydrolase Activity and Penicillin Tolerance

Abstract: Previous studies in our laboratory have shown that the Staphylococcus aureus LytSR two-component regulatory system affects murein hydrolase activity and autolysis. A LytSR-regulated dicistronic operon has also been identified and shown to encode two potential membrane-associated proteins, designated LrgA and LrgB, hypothesized to be involved in the control of murein hydrolase activity. In the present study, a lrgAB mutant strain was generated and analyzed to test this hypothesis. Zymographic and quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
314
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 216 publications
(327 citation statements)
references
References 38 publications
(37 reference statements)
9
314
4
Order By: Relevance
“…In previous studies, it was shown that a lytS mutation resulted in altered murein hydrolase activity, increased Triton X-100-and penicillin-induced lysis, and undetectable lrgAB transcription (3,4,11). Given that the lrgAB operon is located immediately downstream of the lytSR locus (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies, it was shown that a lytS mutation resulted in altered murein hydrolase activity, increased Triton X-100-and penicillin-induced lysis, and undetectable lrgAB transcription (3,4,11). Given that the lrgAB operon is located immediately downstream of the lytSR locus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, Northern blot analyses were used to compare lrgAB mRNA levels in agr and sar mutants and the parental wild-type strain. Using a lrgAB-specific probe, the level of lrgAB transcription was monitored in late-exponential-phase cells, when the lrgAB operon is maximally expressed (11). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations